Indian culture and society in R. K. Narayan’s (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Despite his attempts at short tales and other forms of literature, RK Narayan became recognized in the West for his novels, such as Mr. Sampath and Guide, written in Indo-English. The works of Narayan are gathered in six volumes: Dodu and other tales, Malgudi days, hurricanes and other stories, Lawley Road and other stories, Star Day and other stories, Horse and two goats, and Star Day and other stories. R. K. Narayan was born during the Indian independence movement (Rashipuram Krishnaswamy Narayanswami Iyer, 1906-2001). Amidst the enormous ferment and joy of that century, three shining stars English literature, Indian lights, and authors Mulk Raj Anand, R. K. Narayan, and Raja Rao began penning their own tales. Among their first responsibilities will be to catalogue the issues and circumstances that beset India and its inhabitants in the early decades of the twentieth century. In some way or another, their myths have all dealt with the subject of ageing. One may discover an accurate portrayal of modern Indian life, culture, and history in R. K. Narayan's writings. Less and less social reality was explained. As a storyteller and artist, Narayan tells the truth with an absolutely remarkable cadence. Pure and unbiased observation reveals everything about social norms and actuality.